The effects of eight weeks of phosphatidic acid, leucine, beta-hydroxy-beta-methylbutyrate, and vitamin D3 supplementation on blood pressure, triglycerides, and total cholesterol in resistance trained males - Escalante, Guillermo; Alencar, Michelle; Haddock, Bryan; Harvey, Phillip (Progress in Nutrition, 2020)
Objective: MaxxTOR® (MT) is a multi-ingredient supplement that contains phosphatidic acid (PA) as the main active ingredient as well as leucine, beta-hydroxy-beta-methylbutyrate, and vitamin D3. The effects of MT on blood pressure, total cholesterol (TC), and triglycerides (TG) were examined.  Methods: Eighteen healthy strength-trained males were randomly assigned to a group that consumed MT (n = 8, 22.0 +/- 2.5 yrs; 175.8 +/- 11.5 cm; 80.3 +/- 15.1 kg) or a placebo (PLA) (n = 10, 25.6 +/- 4.2 yrs; 174.8 +/- 9.0 cm; 88.6 +/- 16.6 kg) as part of a double-blind, placebo controlled pre/post experimental investigation. Systolic blood pressure (SBP), diastolic blood pressure (DBP), and blood samples were taken from the participants at week 0 and week 9 of the study to determine the effects of MT on cardiovascular risk factors. Blood serum was analyzed for TC and TG. Subjects were placed and monitored on a eucaloric diet consisting of 25% protein, 50% carbohydrates, and 25% fat by a registered dietitian. Separate two-way mixed factorial repeated measures ANOVA’s (time (Pre, Post) x group (MT and PLA) were used to investigate SBP, DBP, TC, and TG changes. Analysis were performed via SPSS (version 22) with significance at p ≤ 0.05. Results: No significant differences were noted between MT and PLA groups for SBP, DBP, TC, or TG. Conclusion: Results suggest that the addition of MT to a 3-day per week resistance training program do not significantly affect SBP, DBP, TC, or TG after eight weeks.